Decision Making and Defensive Effectiveness of Ball Screen in Top-Level Basketball - Nunes H; Iglesias X; Anguera M.T (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
The objective of this study is to analyze the effectiveness of the defensive actions of the pick and roll in basketball by ACB League teams throughout a full season (2010-11), contrasting the results obtained with the opinion of basketball experts on the decision-making process regarding this game action. The research uses direct observation (observational methodology) and indirect observation (in-depth interviews). An observational instrument is used to analyze the actions of pick and roll and this is recorded using the software Dartfish TeamPro v.4.5. For the in-depth interviews, an indirect observation instrument is built and validated. The significant association between different elements of the game and defensive efficiency is determined using Chi-square and a polar coordinate analysis. 8267 actions have been analyzed, of which 26.9% correspond to ball screens. Significant differences (p <.05) are detected in the distribution of the different types of defensive aid from the defender of the ball handler and the defender of the screener in relation to defensive effectiveness, the most widely used option being the chase and the show. The coaches express in their in-depth interviews why “pick and roll is such a widely used and effective action” (Scariolo).